Formation Of The Concept Of Independent, Wise, Innovative, And Resilient Human Resources In Gen Z: Digital Multi-Stakeholder Cooperatives For Business Knowledge Management - Sumantri, Bambang Agus; Anas, M.; Yulianto, Dema; Riani, Lilia Pasca (Journal of Ecohumanism, 2025)
"How do the characteristics of Gen Z interpret the digital multi-party cooperative business model?" is the topic this study aims to address. In light of the challenges posed by the community demographic bonus, including changes in the characteristics of Generation Z, the development of cooperative business models and cooperative dynamics in Indonesia is urgently needed. In order to do this, it is necessary to analyze the characteristics of Gen Z as they enter the world of digital multi-party cooperatives that concentrate on the context of Business Knowledge Management (BKM). The research is qualitative and descriptive in nature. A literature review serves as the research model. Data collection makes advantage of online literature discovery, which may be found in e-books, articles from the media, research journals, the ideas of Resilient, Innovative, Independent, and Wise are connected to Business Knowledge Management (a 21st century competency in the 6c character framework) for digital multi-stakeholder cooperatives following the data analysis of the three stages previously described. evaluated using a linkert scale of 5 on a questionnaire. by employing a Google Form that was completed by 520 Indonesian students and analyzed with Smart-PLS. This essay concludes that, particularly in the context of multi-stakeholder cooperatives, Generation Z possesses strong and pertinent traits to actively participate in corporate knowledge management and innovation in the digital age.